Ambidextrous Innovation and Business Resilience: A Systematic Literature Review - Rahmat Hidayatullah; Siti Aliyati Bushairi; Nuril Huda; M Riza Firdaus (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2026)
Business resilience has become a key priority for organizations now that they have to deal with constant turbulence, digital disruptions, and crises. However, prior studies have not been able to cohesively analyze how ambidextrous innovation enhances resilience and more specifically, in what contexts this is more or less the case. This study attempts to address the fragmented research by providing a systematic review of the literature in 20 journal articles. The review identifies four recurrent themes. First, ambidextrous innovation helps to improve business resilience by helping organizations manage both exploratory and exploitative innovation. Second, ambidextrous innovation can act as a mediating capability in the digital, technological, and strategic components of resilience. Third, business resilience can act as a mediating mechanism that helps to transform the various components of ambidextrous innovation into desirable outcomes, such as organizational performance, innovation performance, and quality growth. Lastly, the impact of these relationships is dependent on contextual influence such as turbulence, intensity of digitalization, the level of available knowledge and the available resources. The review also identifies the presence of dynamic capability, cross-sectional studies, and a focus on emerging economies with a direct focus on China and the small and medium sized enterprise (SME) sector. The paper synthesizes the fragmented research and proposes a preliminary framework and research focus to advance the study of resilience in a constructive and context relevant manner.